1977
DOI: 10.1192/bjp.130.2.184
|View full text |Cite
|
Sign up to set email alerts
|

Obsessional Cognition: Performance on Two Numerical Tasks

Abstract: It is argued that obsessional indecision reflects a formal cognitive characteristic, and should therefore be detectable in slower performance of insignificant, neutral tasks. The obsessional will not be handicapped in structured tasks requiring concentration and a deductive approach, but he will be slower in less structured tasks requiring a predominantly inductive approach. Results from two neutral (numerical) tasks support the predictions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 1 publication
0
21
0
Order By: Relevance
“…Finally, more standard forms of testing reasoning have examined how participants draw conclusions using fixed premises in a deductive format and how people use abstract forms of reasoning (when solving arithmetic problems for example). Formal reasoning was examined by Reed (1977) where OCD and psychiatric control participants were tested on their deductive and inductive reasoning performances. Differences between the two groups were observed in the deductive reasoning arithmetic task where the OCD group performed better, and in the inductive task where their performance was inferior to the psychiatric control group.…”
Section: Reasoning In Ocdmentioning
confidence: 99%
“…Finally, more standard forms of testing reasoning have examined how participants draw conclusions using fixed premises in a deductive format and how people use abstract forms of reasoning (when solving arithmetic problems for example). Formal reasoning was examined by Reed (1977) where OCD and psychiatric control participants were tested on their deductive and inductive reasoning performances. Differences between the two groups were observed in the deductive reasoning arithmetic task where the OCD group performed better, and in the inductive task where their performance was inferior to the psychiatric control group.…”
Section: Reasoning In Ocdmentioning
confidence: 99%
“…No robust evidence exists that patients with obsessive compulsions are poorer at reasoning than other individuals (see, e.g., the empirical studies of Reed, 1977). Their reasoning starts with a thought about potential danger that appears to come from nowhere, just as many thoughts do in daily life, and it contains a kernel of rational anxiety.…”
Section: Obsessive-compulsive Disordermentioning
confidence: 99%
“…Individuals with obsessional symptoms ask for significantly more repeats of a trial than those without obsessional symptoms, consistent with the prediction that obsessional individuals will demand more information to arrive at a decision than nonobsessional individuals. Similarly, Reed (1977a) showed that decision difficulty experienced by the obsessional individual is inversely related to the amount of structuring available in the task itself. Deductive tasks present little difficulty because the task itself provides inherent logical closure.…”
Section: Conceptualizations Of Ocd As a Cognitive Disordermentioning
confidence: 99%